2007
DOI: 10.1063/1.2712941
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetoelastic properties of Ga-substituted cobalt ferrite

Abstract: Magnetic and magnetoelasticproperties of a series of Ga-substituted cobaltferrites,CoGaxFe2−xO4 (x=0.0-0.8), have been investigated. The Curie temperatureTCand hysteresis properties were found to vary with gallium content (x), which indicates that exchange and anisotropy energies changed as a result of substitution of Ga for Fe. The maximum magnitude of magnetostriction decreased monotonically with increasing gallium content over the range x=0.0-0.8. The rate of change of magnetostriction with applied magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…However, the highest maximum strain obtained for the sample is very low as 150 ppm. Enhancement in the strain sensitivity is reported after substitution of metal ions in the cobalt ferrite lattice, but at the cost of the magnetostriction strain [13][14][15][16][17]. It has been shown that the strain sensitivity can be enhanced, without affecting the magnetostriction coefficient, for sintered Mn-substituted cobalt ferrite made from nanosized powders [18].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the highest maximum strain obtained for the sample is very low as 150 ppm. Enhancement in the strain sensitivity is reported after substitution of metal ions in the cobalt ferrite lattice, but at the cost of the magnetostriction strain [13][14][15][16][17]. It has been shown that the strain sensitivity can be enhanced, without affecting the magnetostriction coefficient, for sintered Mn-substituted cobalt ferrite made from nanosized powders [18].…”
Section: Introductionmentioning
confidence: 94%
“…4 shows the variation of the saturation magnetization (M s ), at room temperature as well as at 5 K, as a function of the Al content in CoFe 2-x Al x O 4 . Saturation magnetization is obtained by extrapolating the [14,22] in cobalt ferrite reduces the net magnetization of the A-site at a greater magnitude than at the B-site. At higher concentrations of the substituted ions, the overall magnetization decreases due the migration of the non-magnetic ions into the B-sites.…”
Section: Magnetic Characterizationmentioning
confidence: 99%
“…Substitution of other metals for Fe in cobalt ferrite has been proposed to tailor the electrical, magnetic, and magnetomechanical properties of such materials. [14][15][16][17][18][19][20][21][22][23] In this context, partial replacement of Fe 3þ by rare earth or large ionic radius ion in the spinel structure has been reported to lead to structural distortion, which induces strain and significantly modifies the electrical properties. [14][15][16] The structural, magnetic, electrical, and dielectric properties of Co ferrites play a key role in the designing of magnetic, electronic, microwave, and electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Since the magnetostrictive properties of CoFe 2 O 4 depend largely on the position and concentration of the Co 2+ ions, it follows that changes in the site occupancy of these ions will affect the magnetic and magnetostrictive properties of CoFe 2 O 4 . Studies have shown that magnetic and magnetostrictive properties can be altered by both chemical substitutions of the cations [4][5][6] and by heat treatment [7,8], the latter leading to a different distribution of cations as they migrate towards their most stable (that is the lowest energy) state. The time constants associated with this process are prohibitively long at room temperature, but are reduced at elevated temperature because of the higher thermal energy per ion which enables them to migrate more easily.…”
Section: Introductionmentioning
confidence: 99%